Hubungan Kualitas Tidur dan Tindakan Olahraga dengan Tingkat Stres Mahasiswa pada Masa Pandemi Covid-19 - Ratutama, Smelta Gresa; Qomaruddin, Mochammad Bagus (Preventif : Jurnal Kesehatan Masyarakat, 2022)
Since the covid-19 pandemic came, the most schools and universities in Indonesia conducted online learning. Online learning has negative impact on college students, that is college students are prone to stress. The aim of this research is to analyze the correlation between quality of sleep and exercise with stress in college student during the covid-19 pandemic. This is a descriptive analysis research with quantitative approach. Design of this research is cross sectional design. This research was conducted in Madiun on November 2020 until Juli 2021. Respondent in this research are college students who stayed in Madiun during the covid-19 pandemic. This research was being analyzed by cross tabulation. The results of this research indicated that the most stess level in respondent is hard level of stress, that is 53,9%. This research showed that sex, age, quality of sleep, and exercise were correlated with stress respondent. The conclusion of this research is that the factors correlated with stress respondent are sex, age, quality of sleep, and exercise.